HOXC11–SRC-1 regulation of S100beta in cutaneous melanoma: new targets for the kinase inhibitor dasatinib - deBlacam, C (Nature Publishing Group, 2011)
BACKGROUND: Cutaneous melanoma is an aggressive disease. S100beta is an established biomarker of disease progression; however, the mechanism of its regulation in melanoma is undefined. METHODS: Expression of HOXC11 and SRC-1 was examined by immunohistochemistry and immunofluorescence. Molecular and cellular techniques were used to investigate regulation of S100beta, including, western blot, qPCR, ChIP and migration assays. RESULTS: Expression levels of the transcription factor HOXC11 and its coactivator SRC-1 were significantly elevated in malignant melanoma in comparison with benign nevi (P<0.001 and P=0.017, respectively, n=80), and expression of HOXC11 and SRC-1 in the malignant tissue associated with each other (P<0.001). HOXC11 recruitment to the promoter of S100beta was observed in the primary melanoma cell line SKMel28. S100beta expression was found to be dependant on both HOXC11 and SRC-1. Treatment with the Src/Abl inhibitor, dasatinib, reduced HOXC11–SRC-1 interaction and prevented recruitment of HOXC11 to the S100beta promoter. Dasatinib inhibited both mRNA and protein levels of S100beta and reduced migration of the metastatic cell line MeWo. CONCLUSION: We have defined a signalling mechanism regulating S100beta in melanoma, which can be modulated by dasatinib. Profiling patients for expression of key markers of this network has the potential to increase the efficacy of dasatinib treatment.